Long pentraxin PTX3 attenuates ischemia reperfusion injury in a cardiac transplantation model. (29th October 2013) - Zhu, Hongfei; Cui, Dan; Liu, Kebin; Wang, Li; Huang, Lili; Li, Jinjie
Summary Ischemia reperfusion (IR) injury is a major issue in cardiac transplantation, and inflammatory processes play a major role in myocardial IR injury. Long pentraxin‐3 (PTX3) is a member of a phylogenetically conserved group of acute‐phase reactants that are involved in inflammation and innate immunity. In our study, hearts of C57Bl/6 mice were flushed and stored in cold Bretschneider solution for 8 h and then transplanted into syngeneic recipient. We found that both mRNA and protein levels of PTX3 were increased following myocardial IR injury; neutralizing antibody against PTX3 aggravated cardiomyocyte apoptosis and recruitment of neutrophils and macrophages. Troponin T (TnT) production on 24 h after myocardial IR injury was reduced by exogenous PTX3 administration and increased by PTX3 neutralization in comparison with control. Cardiac output at 60 mmHg of afterload pressure was also increased in hearts with exogenous PTX3 administration and decreased with PTX3 neutralization (PTX3: 58.4 ± 7.4 ml/min; Control: 24.5 ± 3.8 ml/min; Anti‐PTX3: 11.6 ± 1.7 ml/min; P < 0.05). Furthermore, PTX3 restricted expansion of γδ T cell that was the major source of IL‐17A and down‐regulated expression of IL‐23 and IL‐17A. In conclusion, PTX3 played a protective role in cardiomyocyte IR injury. PTX3 ameliorated cardiomyocyte apoptosis and infiltration of neutrophil and macrophage and then improved hemodynamic performance. This was associated with restricted γδ T‐cell expansion and decreased IL‐23/IL‐17A expression.